Willingness to use HIV pre-exposure prophylaxis has declined among Australian gay and bisexual men: Results from repeated national surveys, 2011-2013 - Holt, M.; Lea, T.; Murphy, Dean; Ellard, J.; Rosengarten, M.; Kippax, S.; De Wit, J. (Lippincott Williams & Wilkins, 2014)
We surveyed willingness to use pre-exposure prophylaxis (PrEP) and the likelihood of decreased condom use among Australian gay and bisexual men in 2011 and 2013 (n = 2384). Willingness to use PrEP declined from 28.2% to 23.3% [adjusted odds ratio = 0.83, 95% confidence interval (CI): 0.68 to 1.00, P = 0.050]. Willingness to use PrEP was the greatest among men with HIV-positive partners and among those who had taken HIV postexposure prophylaxis. Among men willing to use PrEP, the likelihood of decreased condom use remained stable between 2011 and 2013 (8.0% vs. 11.9%; adjusted odds ratio = 1.40, 95% CI: 0.80 to 2.45, P = 0.23). A minority of men remain willing to use PrEP and appear to be appropriate candidates for it.